Public investment on irrigation and poverty alleviation in rural Laos - Bounmy Inthakesone; Pakaiphone Syphoxay (Journal of Risk and Financial Management, 2021)
The demand for water is rising rapidly, particularly in agricultural and environmental sectors. This has led to more competition to access limited and scarce water resources. Therefore, choosing an appropriate approach to manage water resources, distribution and allocation, to attain sustainable agriculture is critical for every country worldwide. The most well-known method to preserve or store water and adaptation strategy to climate change is irrigation. This paper wished to understand the impact of irrigation on farmers' income in Laos, especially from rice, which is the main crop of rural people. The difference in differences (DID) method was employed to estimate the regression results. The DID was estimated by the pooled OLS of the effect on the log of households' rice farm income and log of households' total income with household head's age, education, gender, household size, ethnicity and harvest areas variables pointing out the coefficients of the outcome variables of interest (after treatment) were 0.037 and 0.076 with positive sign but statistically insignificant. The result implies irrigation has no impact on rice products. In other words, irrigation does not increase households' income. The finding indicates the type of irrigation, the location of the operation headquarters and the management system or governance are crucial factors for explaining the impact of irrigation on the rice products in Laos.
Keywords: 330; difference in differences; irrigation; panel data; public investment; rice productions; total income